Impact of warm‐season grass management on feedstock production on marginal farmland in Central Illinois. Issue 10 (24th June 2019) - Zumpf, Colleen; Lee, Moon‐Sub; Thapa, Santanu; Guo, Jia; Mitchell, Rob; Volenec, Jeffrey J.; Lee, DoKyoung
Abstract: The production of dedicated energy crops on marginally productive cropland is projected to play an important role in reaching the US Billion Ton goal. This study aimed to evaluate warm‐season grasses for biomass production potential under different harvest timings (summer [H1], after killing frost [H2], or alternating between two [H3]) and nitrogen (N) fertilizer rates (0, 56, and 112 kg N/ha) on a wet marginal land across multiple production years. Six feedstocks were evaluated including Miscanthus x giganteus, two switchgrass cultivars ( Panicum virgatum L .), prairie cordgrass ( Spartina pectinata Link), and two polycultures including a mixture of big bluestem ( Andropogon gerardii Vitman), indiangrass ( Sorghastrum nutans ), and sideoats grama ( Bouteloua curtipendula [Michx.] Torr.), and a mixture of big bluestem and prairie cordgrass. Across four production years, harvest timing and feedstock type played an important role in biomass production. Miscanthus x giganteus produced the greatest biomass (18.7 Mg/ha), followed by the switchgrass cultivar "Liberty" (14.7 Mg/ha). Harvest in H1 tended to increase yield irrespective of feedstock; the exception being M. x giganteus that had significantly lower biomass when harvested in H1 when compared to H2 and H3. The advantage H1 harvest had over H2 for all feedstocks declined over time, suggesting H2 or H3 would provide greater and more sustainable biomass production for the observed feedstocks. The N application rate played an important role mainly for M. x giganteus where 112 kg N/ha yielded more biomass than no N. Other feedstocks occasionally showed a slight, but statistically insignificant increase in biomass yield with increasing N rate. This study showed the potential of producing feedstocks for bioenergy on wet marginal land; however, more research on tissue and soil nutrient dynamics under different N rates and harvest regimes will be important in understanding stand longevity for feedstocks grown under these conditions. Abstract : Biomass yield potential of six warm‐season grass feedstocks affected by harvest management on wet marginal land.